Plasma receptor for advanced glycation end products and clinical outcomes in acute lung injury. Issue 12 (19th June 2008) - Calfee, C S; Ware, L B; Eisner, M D; Parsons, P E; Thompson, B T; Wickersham, N; Matthay, M A; ,
Abstract : Objectives: To determine whether baseline plasma levels of the receptor for advanced glycation end products (RAGE), a novel marker of alveolar type I cell injury, are associated with the severity and outcomes of acute lung injury, and whether plasma RAGE levels are affected by lower tidal volume ventilation. Design, setting and participants: Measurement of plasma RAGE levels from 676 subjects enrolled in a large randomised controlled trial of lower tidal volume ventilation in acute lung injury. Measurements and main results: Higher baseline plasma RAGE was associated with increased severity of lung injury. In addition, higher baseline RAGE was associated with increased mortality (OR for death 1.38 (95% CI 1.13 to 1.68) per 1 log increment in RAGE; p = 0.002) and fewer ventilator free and organ failure free days in patients randomised to higher tidal volumes. These associations persisted in multivariable models that adjusted for age, gender, severity of illness and the presence of sepsis or trauma. Plasma RAGE was not associated with outcomes in the lower tidal volume group (p = 0.09 for interaction in unadjusted analysis). In both tidal volume groups, plasma RAGE levels declined over the first 3 days; however, the decline was 15% greater in the lower tidal volume group (p = 0.02; 95% CI 2.4% to 25.0%). Conclusions: Baseline plasma RAGE levels are strongly associated with clinical outcomes in patients with acute lung injury ventilated with higher tidal volumes. Lower tidal volume ventilation may be beneficial in part by decreasing injury to the alveolar epithelium.